2016
DOI: 10.1542/peds.2015-4343
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and Academic Outcomes at Age 10 Years of Extremely Preterm Newborns

Abstract: for the ELGAN Study Investigators abstract BACKGROUND AND OBJECTIVE: Despite reductions in mortality and morbidity among children born extremely preterm, they remain at high risk of neurocognitive deficits, with up to 40% having significant cognitive deficits at school age. We assessed the rate of neurocognitive impairment in a contemporary US cohort of 873 children aged 10 years who were born <28 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 47 publications
6
80
0
Order By: Relevance
“…Most of the other studies of reading skills among VLBW and ELBW children have been cross‐sectional . They suggested that most reading skills were adversely affected among these children, but they were not designed to address the developmental course .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the other studies of reading skills among VLBW and ELBW children have been cross‐sectional . They suggested that most reading skills were adversely affected among these children, but they were not designed to address the developmental course .…”
Section: Discussionmentioning
confidence: 99%
“…When they were 10 years old, we recruited the 966 of the children for whom we had measurements of inflammation markers in blood specimens collected during the first postnatal month. Of the 996 eligible children, 889 children (89%) were enrolled (10,11). They constitute the sample for this report.…”
Section: Participantsmentioning
confidence: 99%
“…(40)(41)(42)(43)(44) Further, despite efforts to improve physiologic stability,(41, 45-52) the rate of neurodevelopmental derangements among extremely preterm infants remains high in numerous studies. (43,44,(53)(54)(55)(56)(57) Second, high SNAP-II scores are associated with postnatal events such as bacteremia/sepsis, necrotizing enterocolitis, and chronic lung disease, (4,58) which are associated with adverse brain-related outcomes. (59)(60)(61)(62) In this way, SNAP-II could be viewed as a marker for subsequent neonatal adversities.…”
Section: Possible Explanations For Our Findingsmentioning
confidence: 99%